Definitive radiotherapy for locally advanced squamous cell carcinoma of the vulva and technical issues: a case report - Appalanaido, Gokula Kumar; I, Norhafizah; I, Shazril; AR, Nursyatina; MZ, Abdul Aziz; Mohd Zin, Mohd Hafiz; MK, Zakir; J, Norjayadi; AS, Norliza; A, Ismail; N, Khairun (IOP Publishing, 2017)
This case report describes a complex radical 3D-Conformal Radiotherapy treatment planning, dosimetric issues and outcome of definitive treatment of un-resectable carcinoma of the vulvar in a 42-year old lady. The patient presented with large fungating mass of the vulva which was biopsy confirmed as Keratinizing Squamous Cell Carcinoma. Further staging investigation revealed locally advanced disease (T4), with bilateral inguinal lymph nodes involvement. There is no systemic metastasis or intra-pelvic nodes. The patient was seen by Gynae-Oncology team and the disease was deemed un-resectable without significant morbidity. She was treated to a total dose of 64.8Gy in 36 fractions over 7 weeks with concurrent weekly Cisplatinum in 2 phases. 3D-Conformal radiotherapy technique using the modified segmental boost technique (MSBT, large PA and small AP photon fields with inguinal electron matching) was used. TLD chips were used for in-vivo dose verification in phase 1 and 2 of the treatment. At completion of planned radiotherapy, patient had a complete clinical response, grade 2-3 skin toxicity, grade 2 rectal toxicity, and grade 2 dysuria Vulval Squamous Cell Carcinomas are very radiosensitive tumours and the skills of the treating Radiation Oncologist, Dosimetrists, Physicist, Radiation Therapist and also nurses is of foremost importance is ensuring good clinical outcomes.